Global Structure of Positive Solutions of a Discrete Problem with Sign-Changing Weight. (15th August 2011) - Ma, Ruyun; Gao, Chenghua; Han, Xiaoling; Chen, Xiaoqiang
Abstract : LetT > 5 be an integer, 𝕋 = { 1, 2, …, T } . We are concerned with the global structure of positive solutions set of the discrete second-order boundary value problemsΔ 2 u ( t - 1 ) + r m ( t ) f ( u ( t ) ) = 0,     t ∈ 𝕋,     u ( 0 ) = u ( T + 1 ) = 0, wherer ∈ ℝ is a parameter, m : 𝕋 → ℝ changes its sign andm ( t ) ≠ 0   for     t ∈ 𝕋 .